Effect of Doping Concentration on Grain Boundary Conductivity of Samaria Doped Ceria Composites. Issue 12 (30th December 2021) - Vinchhi, Prerna; Patel, Roma; Mukhopadhyay, Indrajit; Ray, Abhijit; Pati, Ranjan
Abstract : This work aims to study the effect of Sm 3+ doping concentration on the grain boundary ionic conductivity of ceria. The materials were prepared by a modified co-precipitation method, where molecular water associated with the precursor has been utilized to facilitate the hydroxylation process. The synthesized hydroxide/hydrated oxide materials were calcined and the green body (pellet) has been sintered at high temperature in order to achieve highly dense (∼ 96%) pellet. The structural analyses were done using XRD and Raman spectroscopy, which confirm the single phase cubic structure of samaria doped ceria (SDC) nanoparticles and the surface morphology of sintered samples was studied using FESEM. The ionic conductivity was measured by AC impedance spectroscopy of the sintered pellets in the temperature range of 400 °C–700 °C, which shows superior grain boundary conductivity. The grain boundary ionic conductivity of around 0.111 S cm −1 has been obtained for 15SDC composition at 600 °C.